O efeito neuroprotetor do exercício físico em ratos submetidos ao modelo animal de fibromialgia induzido por reserpina - Moreira, Karen Luise dos Santos (2018)
Fibromyalgia (FMS) is a musculoskeletal syndrome characterized by generalized chronic primary pain. In this pathology, dysfunction occurs in the pain inhibitory system, reducing monoamines, such as serotonin (5-HT), which is produced by neurons located in raphe nuclei, including the nucleus raphe magnus (NRM) which sends projections to the dorsal horn of the spinal cord, where modulation of ascending pain information occurs. Pharmacological treatment in FMS is not effective, so physical exercise is indicated as a non-pharmacological intervention, aiming to improve the quality of life of patients suffering from fibromyalgia. However, there are no studies demonstrating the neuroprotective relationship of physical exercise in FMS or effective methods to prevent FMS. Considering the importance of 5-HT and its activity in the central nervous system (CNS), the objective of this study was to evaluate the effect of reserpine on mechanical and nociceptive sensitivity, locomotor activity and immunoreactivity to 5-HT in NRM; as well as to evaluate the effect of physical exercise on treadmill, before reserpinization, for 14 days in male Wistar rats. The animals were divided into three groups: control (no-reserpinized; C); Reserpinized (R) and Trained-Reserpinized (TR). At the end of the training protocol the animals were reserpinized and the mechanical sensitivity (von Frey filaments and Randall-Selitto test), nociceptive sensitivity (tail-flick test), exploratory and locomotor activities (open field test), optical density and the number of 5-HT immunoreactive neurons in NRM (by immunohistochemistry technique) were analyzed. After performing the appropriate statistical analysis, was observed that the application of reserpine did not alter the body weight and mobility of the animals; reserpine increases mechanical and nociceptive sensitivity, and decreases the number of 5-HT positive neurons in NRM. All of these changes were prevented by treadmill training. In conclusion, physical training prior to reserpine, prevents behavioral and morphological changes caused by reserpine, showing the neuroprotective effect of physical exercise.